Compression socks enhance sensory feedback to improve standing balance reactions and reflex control of walking - Yao Sun; Bridget Munro; E. Paul Zehr (BMC, 2021)
Abstract Background Compression garments are generally used for their potential benefits in exercise performance and post-exercise recovery. Previous studies show that compression sleeves worn at the elbow change neuromuscular control and improve performance during reaching movement. Cutaneous stimulation of the foot skin produces location-specific reflexes in the lower limb that guide foot placement during locomotion. However, it is not clear whether enhancement of sensory feedback with compression socks can alter the neuromuscular excitability of muscles in the leg and amplify balance performance and walking. The current project aimed to determine whether enhanced sensory input from wearing compression socks could affect: 1) spinal cord excitability (as measured by cutaneous reflexes from stimulation at the top or bottom of the foot during locomotion); 2) static balance performance; and, 3) dynamic balance performance following virtual perturbations. Methods Twelve participants completed walking and balance tasks wearing four types of garments: 1) non-compression (control) socks; 2) ankle compression socks; 3) calf-compression socks; and, 4) customized ankle sleeves. During walking, electrical stimulations were delivered to three discrete locations on the dorsal (ankle crease, forefoot medial) and plantar (forefoot medial) surfaces of the foot in separate trials with each garment. Electromyography of ankle dorsiflexor tibialis anterior, plantarflexor medial gastrocnemius and evertor peroneus longus were measured bilaterally along with kinematic data from knee and ankle and kinetics under the right (stimulated) foot. Results Compared to control socks, altered cutaneous reflexes and biomechanical responses were observed in all the conditions during walking. In dynamic balance tests, time and integrated EMG for recovering from virtual perturbation were significantly reduced when wearing calf compression socks and the ankle sleeve. Conclusions Our findings suggest sensory enhancement from compression garments modifies spinal cord excitability during walking and improves performance in balance recovery after virtual perturbation.